IMPROVING THE RELIABILITY OF DURABILITY PREDICTION OF BUILDING MATERIALS AND STRUCTURES AS ONE OF THE FACTORS OF SUSTAINABLE ECONOMIC DEVELOPMENT - A.V., Erofeev; Sergeevna, Mishchenko Elena; N., Apraksina O.; N., Urda M.; V., Polivanova T. (Journal of Applied Engineering Science, 2020)
During operation, building materials and structures in buildings and structures are exposed to a whole range of adverse effects, leading to the loss of their performance characteristics. It is shown that at present there is a possibility to predict the durability of building materials and structures already at the stage of their design without carrying out additional inspections during operation. This prediction is based on the concept thermofluctuational destruction and deformation of the solid body. Experimental studies are presented to determine the effect of temperature and stress on the value of durability for polyvinyl chloride plates during cross bending, on the basis of which the thermal fluctuation constants of the generalized Zhurkov equation are found by three different methods. A comparative analysis of them is made and a method for their determination is proposed, which makes it possible to increase the accuracy of the durability prediction.